Estudio de factibilidad de instalacion de sistemas fotovoltaicos en viviendas tipo de la ciudad autonoma de Buenos Aires - Pilar, Claudia Alejandra; Vera, Luis Horacio; Martínez, Cinthia Alejandra; Poladian, Andrés (Universidad Nacional del Nordeste. Facultad de Arquitectura y Urbanismo. Instituto de Investigaciones Tecnológicas para el Diseño Ambiental del Hábitat Humano, 2022)
Amongst renewable energies, photovoltaic solar energy connected to the grid is of the ones that has major possibilities of integration to urban environment, where most of electrical demand is generated. In this article, we evaluate the technical possibilities of incorporating an on-grid connected photovoltaic system in an standard residential building of the City of Buenos Aires, for serving the common areas of it, considering options of power and orientation. According to our analysis, it would be feasible to feed common spaces of the building. From a technical point of view, it is necessary to evaluate: inclination, the more favorable orientations, and to perform shadow analysis in order to optimize the operation of the system. While the initial investment is a negative factor by now, costs are getting more and more competitive, as much as incipient lines of credit emerge and a cultural change is foreseen, with greater environmental commitment. Because of all those, we consider that in the near future this type of systems are likely to be implemented.